Answer:
![x = \frac{1}{3}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20)
Step-by-step explanation:
*Move terms to the left and set equal to zero:
4㏒(√x) - ㏒(3x) - ㏒(x²) = 0
*simplify each term:
㏒(x²) - ㏒(3x) - ㏒(x²)
㏒(x²÷x²) -㏒(3x)
㏒(x²÷x² / 3x)
*cancel common factor x²:
㏒(
)
*rewrite to solve for x :
10⁰ = ![\frac{1}{3x}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3x%7D)
1 = ![\frac{1}{3x}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3x%7D)
1 · x =
· x
1x = ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
*that would be our answer, however, the convention is to exclude the "1" in front of variables so we are left with:
x = ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
<h3>
♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫</h3>
➷ 2) The integral of a constant follows this rule:
adx = ax
In this case, it is 1dx = 1x
This can be simplified to just x
Add a constant to this, to get the final answer of:
x + C
3) The integrals power rule is:
![x^adx = \frac{x^a^+^1}{a +1}](https://tex.z-dn.net/?f=x%5Eadx%20%3D%20%5Cfrac%7Bx%5Ea%5E%2B%5E1%7D%7Ba%20%2B1%7D)
Substitute the values in:
![\frac{x^5^+^1}{5 +1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E5%5E%2B%5E1%7D%7B5%20%2B1%7D)
This can be simplified to:
![\frac{x^{6} }{6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B6%7D%20%7D%7B6%7D)
Add a constant to this to get the final answer of:
![\frac{x^{6} }{6} +C](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B6%7D%20%7D%7B6%7D%20%2BC)
<h3><u>
✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
Answer:
Ok hi
Step-by-step explanation:
x=3 and x= -2
Step-by-step explanation:
we could simplify it to x*2 + x -6 = 0
then 2 numbers whose sum is 1 and product is -6
the numbers are 3 and -2